The Responsibility to Protect (R2P) Concept as an Attempt for Protection of Human Rights in International Humanitarian Law Context - Ibnu Mardiyanto; Hidayatulloh Hidayatulloh (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
The 20th century was marked by mass murder and crime to humanity, such as genocide, war crime, and ethnic cleansing, resulting in tens of millions of deaths throughout the world. While the objective of establishing the United Nations in 1945 aimed at preventing such crimes, mass murders kept on occurring, as the cases in Bosnia and Rwanda in 1990s. The responsibility to protect (R2P) concept emerged as a response to these failures, by proposing that the sovereignty of a country should be based on the responsibility to protect its citizens, rather than the right to take actions without any intervention from the international world. This research aims at exploring the R2P concept as an attempt to protect human rights in the international humanitarian law context by analyzing the relevant literature and legal norms to discover how this concept can be the basis for protecting human rights under conflict situation and four mass violations of human rights. It used normative legal research method based on international law framework. Two approaches were used, namely conceptual and comparative ones. The research results indicated that R2P concept was the best alternative for humanitarian intervention to protect mankind from such crimes as genocide, ethnic cleansing, and crimes against humanity. In an intra-country conflict, the international community was responsible through preventive and military intervention attempts. The R2P concept was also relevant in international humanitarian law since it gave a clear framework in protecting human rights and preventing mass crimes, especially in relation to the use of military power.